The Determination of Fe, Si and Al Content in Iron Ore Blastholes by Nuclear Logging - A Rojc; J Ronaszeki; C Smith (The Australasian Institute of Mining and Metallurgy, 2002)
Nuclear logging was tested for the in situ determination of Fe, Si, and Al in iron ore blastholes with field tests at the BHP Billiton Iron Ore, Mount Waleback Mine. Prompt gamma neutron activation analysis (PGNAA) was used to determine percentages of Fe and Si while natural gamma logging was employed for the determination of Al. The accuracy given by nuclear logging is comparable to the accuracy provided by the laboratory analysis which was determined by taking the average of four samples collected from the cuttings deposited on the surface around the perimeter of a drill hole. The work also indicated that there is a chance of determining Al by PGNAA.